Knowledge, Attitude and Mother's Support Relationship with Personal Behavior Genital Organ Hygiene in Adolescent Women - Ulvana, Sukma; Astuti, Dwi; Kusumaningrum, Tanjung Anitasari Indah (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Adolescents experience reproductive organ maturity which is marked by menstruation. Reproductive health problems are the main focus of attention for adolescents. Poor personal hygiene of the genital organs can cause several health problems, such as itching in the vaginal area, vulvitis, and vaginitis caused by irritating substances or objects and infection. The objective of this research was to analyze the relationship between adolescent females’ knowledge and attitude, and maternal support with personal hygiene behavior of genital organs at SMK Citra Medika Sragen. This type of research was an analytic survey with a cross-sectional approach. This research was carried out in March-April 2022 with a population of 553 in grades 10, 11, and 12 at SMK Citra Medika Sragen. The research sample was 243 respondents selected using the proportional random sampling technique. Collecting data using a questionnaire via a google form. The results of data analysis based on the Chi-Squaree test showed that there was a relationship between knowledge of the personal hygiene behavior of genital organs (p=<0,001), there was a relationship between attitudes toward the personal hygiene behavior of genital organs ((p=<0,001), and there was no relationship between maternal support with personal hygiene behavior of genital organs (p=0,536). Knowledge and attitudes related to personal hygiene behavior of genital organs. It is recommended that SMK Citra Medika Sragen adds an educational program on adolescent reproductive health in the school health unit (UKS).